Prophylaxis of Infective Endocarditis: A Cross Sectional Survey among Physician Members of the Portuguese Society of Cardiology - de Sousa, Catarina (2022)
Introduction: In the last decade, the downgrading of indications for antibiotic prophylaxis for infective endocarditis caused an uncertain impact on the incidence of this condition. Since no data is available on the practice of infective endocarditis prophylaxis in Portugal, we aimed to characterize the pattern of antibiotic use for infective endocarditis prophylaxis and the compliance/awareness of scientific guidelines among physician members of the Portuguese Society of Cardiology.Material and Methods: A cross sectional observational study was conducted. An online self-completed questionnaire with 12 items on infective endocarditis prophylaxis was sent to 1330 physicians, specialists and residents, members of the Portuguese Society of Cardiology. In addition, descriptive statistical analysis was performed.Results: Two hundred and fifty-three valid questionnaires were responded. Eighty-seven per cent of respondents were cardiologists (specialists or residents), mostly between 30 and 40 years old (26.7%) and 50 to 80 years old (44.3%). The majority (83.0%) follow the European scientific guidelines. Still, 61.0% had or may have had doubts regarding prophylaxis of infective endocarditis in certain patients. Variable adherence to scientific guidelines was noted. Further scientific evidence was required by 60.6% of respondents.Conclusion: Infective endocarditis prophylaxis was generally guided by European scientific guidelines among physicians of the Portuguese Society of Cardiology. There was, however, an evident discrepancy between the guidelines and real-world perception of the risk of infective endocarditis. This highlights the sensed gap in accessing more robust scientific evidence.